Asuhan Keperawatan Jiwa Pada Pasien Dengan Resiko Perilaku Kekerasan Di Wisma Nuri Rsj Prof.Hb Saanin Padang - Hanifah Wardatul Jannah; Vivi Yuderna; Ramaita .; Dwi Happy Anggia Sari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Risk of violent behavior is one of the psychiatric nursing problems in patients with severe mental disorders caused by the inability to control emotions and aggressive impulses, which may potentially harm themselves, others, or the environment. Based on medical record data at RSJ Prof. HB. Saanin Padang, cases of risk for violent behavior remain relatively high, with more than 100 patients treated each year. This condition indicates that the risk of violent behavior continues to be a serious issue in psychiatric nursing services and requires optimal and continuous management. The purpose of this case study was to obtain an overview of the implementation of psychiatric nursing care for patients with the risk of violent behavior. The method used was a case study approach through the nursing process, including assessment, diagnosis, intervention, implementation, and evaluation. Nursing interventions were provided through deep breathing exercises, hitting pillows, education on medication adherence, effective verbal communication, and spiritual activities. The results showed that the patient became calmer, more cooperative, able to control anger, did not use harsh words, and adhered to medication. It can be concluded that psychiatric nursing care is effective in reducing the signs and symptoms of the risk of violent behavior. Nurses and families are expected to play an active role in supporting treatment and preventing patient relapse.